2010
DOI: 10.1111/j.1524-4741.2009.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

In Newly Diagnosed Breast Cancer, Screening MRI of the Contralateral Breast Detects Mammographically Occult Cancer, Even in Elderly Women: The Mayo Clinic in Florida Experience

Abstract: The role of magnetic resonance imaging (MRI) in patients with newly diagnosed breast cancer is somewhat controversial. The purpose of this study was to evaluate the prevalence of synchronous, occult contralateral breast cancer detected by MRI but not by mammography or clinical breast examination in women with newly diagnosed breast cancer, including those aged 70 years or older at our institution. MRI results for women with newly diagnosed breast cancer who underwent bilateral breast MRI after negative mammogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…The Mayo Clinic in Florida reported that an older age was a risk factor associated with bilateral synchronous malignancy . They found that older patients (>70 years) had a higher rate of contralateral cancer (5.4% versus 3.8%).…”
Section: Discussionmentioning
confidence: 99%
“…The Mayo Clinic in Florida reported that an older age was a risk factor associated with bilateral synchronous malignancy . They found that older patients (>70 years) had a higher rate of contralateral cancer (5.4% versus 3.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Two of those criteria (ILC and high genetic-familial risk) were similarly unconfirmed in a previous study [13], while a third criterion, mammographic density, was not confirmed in multiple previous studies [13,1822]. The 2 other criteria (multifocal/multicentric disease, candidacy for PBI) have not been previously tested as predictors of MMA.…”
Section: Discussionmentioning
confidence: 91%
“…[3][4][5][6][7] It is well-known that mammography/tomosynthesis can miss breast cancers, especially in dense breasts. 23 Preoperative bilateral breast MRI finds 2.2%-5.5% additional contralateral breast cancers when compared to mammography alone, [17][18][19] but its limited access and high cost may create undesirable delays in the preoperative investigation and increases the health care costs. Weinstock et al 24 showed that mammography had a poor sensitivity for the surveillance of the contralateral breast, reiterating the importance of using other imaging methods during the preoperative evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that bilateral synchronous neoplasms are often of the same histological subtype, the contralateral cancer frequently exhibits a different and benign‐looking appearance at imaging when compared to the index lesion . The incidence of synchronous contralateral cancer in the setting of prophylactic contralateral mastectomy is 2.1%‐15.4%, while it is 0.4%‐2% for mammography or physical examination, and 2.2%‐5.5% on magnetic resonance imaging (MRI) . The use of preoperative MRI to detect synchronous contralateral invasive is controversial, given that MRI is expensive in terms of money, examination and staff time, and that it is not readily available in many regions of the world.…”
Section: Introductionmentioning
confidence: 99%